The Effect of Self-Reference on Retrieval of Working Memory in Individuals With Independent Self-Construal - Azzahra, Haifa Audrey; Bestari, Nia Prima; Caroline, Caroline; Muqtafa, Rifa Khoirul; Sulistiobudi, Rezki Ashriyana (Universitas Negeri Malang, 2023)
This research aims to find out the influence of self-referential stimuli on information retrieval from working memory in individuals with independent self-construal as a strategy for storing information in working memory. This research was conducted on 39 students using a within-participants post-test-only experimental design. The measuring instrument used is The Self-Construal Questionnaire with a Cronbach’s alpha reliability value of more than 0.70 and a content validity index between 3–4. Information retrieval (information accuracy and response time) is measured by giving a delayed matched-to-sample working memory task in three different conditions, namely where the information refers to oneself, a friend and a stranger. Based on the average accuracy, information related to friends was found to have the highest accuracy compared to the others. However, from the results of Friedman’s ANOVA test (p less than 0.05), the difference was not significant. The role of collectivist culture in Indonesia can make information with friend references considered more meaningful. Apart from that, there are differences in response time results where strangers require relatively faster time because they are influenced by information processing that involves a broader area of the brain.